The hereditary elite of the kazakh society of the XVII–XIX centuries in the scientific heritage of Irina Yrofeyeva - Zh. B. Kundakbayeva; A. A. Nuratay (Nomadic Civilization: Historical Research, 2021)
The personality and creativity of the Kazakh scientist Irina Viktorovna Yerofeyeva, who recently left us, is considered in this article as an independent object of scientific commemoration. Her range of interests was quite wide, and her scientific heritage was truly unique. In our study, the subject of historiographic analysis was mainly the works of I. Yerofeyeva concerning the hereditary privileged elite of the nomadic society of the Kazakhs in the process of colonial subordination of the Russian Empire, which went on for quite a long historical time. The scientist clearly and precisely raised the question of the strategies of behavior of the national hereditary elite of the Kazakhs in this difficult historical period. I. Yerofeyeva not only presented a full-fledged picture of the elimination of the institution of khan power in Kazakhstan, but also showed how the Russian empire dealt with the “old steppe institution, the estate of the traditional nobility – tore or sultan” in the process of colonial subordination. It was I. Yerofeyeva who raised the question of the mobilizing role of the traditional ruling elite of the Kazakhs in opposing tsarism. According to the scientist, the Russian Empire eventually achieved an important goal set before the beginning of the colonial subordination of the Kazakh steppe. It broke the indisputable privilege of the sultan’s estate that had prevailed for many centuries in the minds of the Kazakhs. “Clear standard criteria for determining the status identification of Kazakh rulers” developed by I. Yerofeyeva are of great importance for the study of the social stratification of the Kazakh society of the imperial period. In general, the analysis of the scientist’s research in the chosen aspect of studying her works definitely showed that Irina Yerofeyeva has forever entered the world science with her outstanding contribution to the study of the history of the Kazakh people at the time of the colonial subordination of Russia, especially its hereditary aristocracy